Bone morphogenetic protein 15 supplementation enhances cumulus expansion, nuclear maturation and progesterone production of in vitro-matured bovine cumulus-oocyte complexes - Delgado, Juliana de Carvalho; Hamilton, Thais Rose dos Santos; Mendes, Camilla Mota; Siqueira, Adriano Felipe Perez; Goissis, Marcelo Demarchi; Buratini, Jose [UNESP]; Assumpcao, Mayra Elena Ortiz D'Avila (Wiley-Blackwell, 2021)
In vitro embryo production (IVP) efficiency is reduced when compared to in vivo. The basic knowledge of bovine in vitro oocyte maturation (IVM) mechanisms provides support to improve in vitro embryo production yields. The present study assessed the effects of bone morphogenetic protein 15 (BMP15), fibroblast growth factor 16 (FGF16) and their combined action on cumulus cells (CC) expansion, oocyte and CC DNA fragmentation, oocyte nuclear maturation, energetic metabolism and progesterone production in bovine IVM. Cumulus-oocyte complexes (COC) were matured in control or supplemented media containing BMP15 (100 ng/ml), FGF16 (10 ng/ml) or BMP15 combined with FGF16; and assessed at 0 and 22 hr of IVM. BMP15 alone or its association with FGF16 enhanced cumulus expansion. BMP15 decreased DNA fragmentation in both CC and oocytes, and improved oocyte nuclear maturation rate. In addition, BMP15 increased CC progesterone production, an effect not previously reported. The present study reinforces previous data pointing to a beneficial influence of BMP15 during IVM, while providing novel evidence that the underlying mechanisms involve increased progesterone production.
Keywords: FGF16; glucose consumption; in vitro maturation; IVM medium; lactate production; oocyte DNA fragmentation